2020
DOI: 10.3748/wjg.v26.i29.4240
|View full text |Cite
|
Sign up to set email alerts
|

Role of long noncoding RNA-mediated competing endogenous RNA regulatory network in hepatocellular carcinoma

Abstract: Long noncoding RNAs (lncRNAs) and microRNAs (miRNAs) are noncoding RNAs (ncRNAs) that occupy over 90% of the human genome, and their main function is to directly or indirectly regulate messenger RNA (mRNA) expression and participate in the tumorigenesis and progression of malignances. In particular, some lncRNAs can interact with miRNAs as competing endogenous RNAs (ceRNAs) to modulate mRNA expression. Accordingly, these RNA molecules are interrelated and coordinate to form a dynamic lncRNA-mediated ceRNA regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 169 publications
0
32
0
Order By: Relevance
“… 32 Growing evidence illuminated that cytoplasmic lncRNAs could operate as ceRNAs for specific miRNAs, thereby upregulating the target mRNAs at the post-transcriptional level. 33–35 Using cell cytoplasmic/nuclear fractionation assay, most NOP14-AS1 was identified to be located in the cytoplasm of TSCC cells, implying that lncRNAs may execute its roles via the ceRNA theory. By searching the ENCORI Starbase 3.0, NOP14-AS1 was found to contain theoretical binding sites of miR-665.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Growing evidence illuminated that cytoplasmic lncRNAs could operate as ceRNAs for specific miRNAs, thereby upregulating the target mRNAs at the post-transcriptional level. 33–35 Using cell cytoplasmic/nuclear fractionation assay, most NOP14-AS1 was identified to be located in the cytoplasm of TSCC cells, implying that lncRNAs may execute its roles via the ceRNA theory. By searching the ENCORI Starbase 3.0, NOP14-AS1 was found to contain theoretical binding sites of miR-665.…”
Section: Discussionmentioning
confidence: 99%
“…8 lncRNAs that act as competing endogenous RNAs (ceRNAs) are able to sequester miRNAs (also called miRNA sponges) via competing with endogenous mRNAs to bind to the miRNA response elements (MREs) in a sequence-specific manner, which results in the reduction of combination between miRNAs and their target mRNAs, and thus weaken the suppressive function of miRNAs on the downstream target gene expressions. 9,10 To date, increasing evidence has identified the carcinogenic or tumor suppressive role of lncRNA-mediated ceRNA networks involved in NSCLC occurrence and dominating crucial cancer hallmark processes like proliferation, apoptosis, angiogenesis, immune escape, drug resistance, as well as epithelial-mesenchymal transition (EMT) and metastasis across NSCLC progression, [11][12][13] accordingly, clarifying the molecular mechanism of the complex "ceRNA-lncRNA-miRNA-mRNA" networks underlying tumor biology will provide novel insight into the potential diagnostic and therapeutic biomarkers of NSCLC (Figure 1). lncRNA prostate androgen regulated transcript 1 (PART1) is located on chromosome 5q12 and is considered to be modulated by androgens and predominantly expressed in the prostate gland.…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence indicated that there are interactions among RNA molecules, such as miRNAs and mRNAs, lncRNAs and mRNAs, and lncRNAs and miRNAs; these RNA molecules collaborate to form a dynamic regulatory network acting as competitive endogenous RNAs (ceRNAs) ( Niu et al, 2020 ). In the present study, a lncRNA-miRNA-mRNA network was built based on the interactions between lncRNA-miRNA, miRNA-mRNA, and lncRNA-mRNA.…”
Section: Discussionmentioning
confidence: 99%